Random logistic maps and Lyapunov exponents - Steinsaltz, D (2001)
We prove that under certain basic regularity conditions, a random iteration of logistic maps converges to a random point attractor when the Lyapunov exponent is negative, and does not converge to a point when the Lyapunov exponent is positive.